Beyond Foucault: Excursions in Political Genealogy - Michael Clifford (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
ca. 200 words; this text will present the book in all promotional forms (e.g. flyers). Please describe the book in straightforward and consumer-friendly terms. [Trump and Trumpism, 21st century warfare, chronic illness, intellectual property: These are just some of the issues examined here. Inspired by the work of Michel Foucault, this book includes articles from scholars employing political genealogy as a methodology and model of theoretical inquiry representing a wide range of disciplines, from the social sciences to the humanities, from philosophy to medicine, to economics, to political and cultural theory. Featuring some of the best and most current work in political genealogy, this work invites us to rethink many of the key concepts in political theory as well as cultural types of expression that we do not routinely think of as political, such as dance, romantic movies, and literature. Broadly conceived, this volume contains essays-excursions, explorations, experimentations-into how political genealogy helps us to understand what Foucault calls "the history of our present," while at the same time looking to our future, to what being a political subject will look like in the 21st century.